ACTIVATION MECHANISMS OF GUT-ASSOCIATED LYMPHOID TISSUE UNDER CHRONIC SOCIAL STRESS CONDITIONS - A. M. Kamyshnyi; I. A. Topol (Медицинская иммунология, 2015)
Stress-induced immune disregulation is a risk factor of autoimmune and inflammatory diseases, but, so far, the mechanisms for this effect are not fully known. Expression levels of specific mRNAs were assessed in gut-associated lymphoid tissue (GALT) from Wistar rats subjected to chronic social stress (CSS). Gene expression was evaluated for NR3C1, Adrβ2, as well as IL-1β, IL-17α pro-inflammatory cytokines, and Nlrp, an inflammasome gene. Under the CSS conditions, we have shown altered distribution of RORγt +, FoxP3+, LMP2+, XBP1+ lymphocytes in GALT.The experiments were carried out with female Wistar rats aged 5–6 months. Specific mRNA expression for the target genes was determined by means of real-time PCR performed in a CFX96™ thermocycler («BioRadLaboratories, Inc»,USA). Relative levels of a target gene expression were quantified by the ΔΔCt method, being compared with rat GAPDH reference gene expression. Statistical analysis was performed with available «BioRad СFX Manager 3.1» software. Specific monoclonal rat antibodes were used for detection of immunopositive lymphocytes by means of indirect immunofluorescence technique.CSS development leads to decreased levels of mRNA expression for Nr3c1 and Adrβ2-genes in the GALT cells, being accompanied with unidirectional changes, i.e., increased transcription of pro-inflammatory cytokine mRNAs (IL-1β, IL-17α) and Nlrp3-inflammasome genes. These changes are accompanied by decreased FoxP3+/RORγt + cell ratio and predominant Th17 differentiation accompanied by suppressor failure. In addition, CSS development was characterized by unidirectional tendency for increasing total number of LMP2+ lymphocytes and reduced ХВР1+ cell population density in lymphoid structures of rat ileum.The events observed in GALT cell populations under CSS conditions are opposing classical paradigm of the stress response. The CSS-associated effects do not promote immunosuppression, however, are able to cause activation of immune system and inflammatory process.